Signs of front‐line healthcare professionals' information anxiety during the COVID‐19 pandemic: Grounded theory study in a Wuhan hospital - Quan Lu; Liang Tao; Xueying Peng; Jing Chen (Wiley, 2024)
Abstract Aim Being front‐line healthcare professionals is associated with possible severe information anxiety during the COVID‐19 pandemic. Investigating signs of information anxiety is the first and key step of its targeted medical intervention. This study aims to explore the signs of front‐line healthcare professionals' information anxiety during the COVID‐19 pandemic. Design This study is qualitative research. Grounded theory was used to classify information anxiety signs of front‐line healthcare professionals. Methods Twenty‐four front‐line healthcare professionals from a general hospital with over 5000 beds in Wuhan were recruited to participate in semi‐structured interviews. According to the frequency and frequency variation of signs appearing in interviews, the trends of signs during the virus encounter, lockdown, flattening and second wave were compared. Based on the interviews, those signs that were conceptually related to each other were extracted to construct a conceptual model. Results Psychological signs (emotion, worry, doubt, caution, hope), physical signs (insomnia, inattention, memory loss, appetite decreased) and behavioural signs (panic buying of goods, be at a loss, pay attention to relevant information, change habits) could be generalized from 13 subcategories of information anxiety signs. Psychological signs were the most in every period of the pandemic. Furthermore, psychological signs decreased significantly during lockdown, while behavioural and physical signs increased. Finally, severe psychological and behavioural signs were associated with physical signs.